Impact of Data from Field Measurements in Numerical Groundwater Modelling: A Case Study in the Kankberg mine, Skellefteå - Andersson, Nora; Persson, Nora (My University, 2024)
The purpose of the study was to evaluate the differences in simulated drawdown pattern, area of influence and mine inflow in a numerical groundwater model using different datasets. The modelled object was the possible expansion Kankberg mine. Simulations were made in three models calibrated to open-source data and field measurements of different quality respectively. The field measurements were used to calibrate the structures of the Kankberg mining system. From the calibrated models, the expansion was added, and results were obtained. It was found that the lower quality data, i.e. the open-source data, was not sufficient to model a correct representation of the current mine. Predictions of mine inflow, drawdown and area of influence with the expansion were considered underestimated. Adding next level of data quality resulted in better predictions of area of influence and drawdown but underestimations in inflow. Similar results were found for the model containing the highest quality of data, which on the other hand was considered under-calibrated. From the study, it was concluded that groundwater level measurements were the most valuable field measurement in groundwater numerical modelling. Measured inflow was considered the second most valuable parameter followed by evaluated hydraulic conductivity. The recommendation suggests a focus on measuring groundwater levels and inflow in the exploration drift when conducting a representative numerical groundwater model in the environmental permit application process for mine construction.
Keywords: numerical groundwater modelling; hydrogeology; MODFLOW-NWT; crystalline bedrock; data value